2019
DOI: 10.1126/science.aau2078
|View full text |Cite
|
Sign up to set email alerts
|

Genetic behavioral screen identifies an orphan anti-opioid system

Abstract: Opioids target the μ-opioid receptor (MOR) to produce unrivaled pain management, but their addictive properties can lead to severe abuse. We developed a whole-animal behavioral platform for unbiased discovery of genes influencing opioid responsiveness. Using forward genetics in Caenorhabditis elegans, we identified a conserved orphan receptor, GPR139, with anti-opioid activity. GPR139 is coexpressed with MOR in opioid-sensitive brain circuits, binds to MOR, and inhibits signaling to heterotrimeric guanine nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 46 publications
3
47
0
Order By: Relevance
“…In situ hybridization experiments showed that GPR139 and MOR are expressed in the same brain regions, including the medial habenula (MHb) and locus coeruleus (LC). Wang et al (2019) further provided electrophysiological evidence to support the functional interaction of MOR and GPR139. In cultured brain slices, GPR139 deficiency reduced the basal firing rate of MHb neurons and increased opioid sensitivity of LC neurons.…”
Section: Mor-gpr139 Heterodimersmentioning
confidence: 82%
See 2 more Smart Citations
“…In situ hybridization experiments showed that GPR139 and MOR are expressed in the same brain regions, including the medial habenula (MHb) and locus coeruleus (LC). Wang et al (2019) further provided electrophysiological evidence to support the functional interaction of MOR and GPR139. In cultured brain slices, GPR139 deficiency reduced the basal firing rate of MHb neurons and increased opioid sensitivity of LC neurons.…”
Section: Mor-gpr139 Heterodimersmentioning
confidence: 82%
“…By whole genome sequencing of these mutants, they identified an orphan receptor FRPR-13 (its homologous protein GPR139 in mammals) as a negative regulator of MOR function in vivo. Wang et al (2019) further investigated the functional interaction of MOR and GPR139 in transfected HEK cells. In transfected HEK293T cells, MOR activation causes hyperpolarization of membrane potential due to opening of the G protein-coupled inwardly-rectifying potassium channels (GIRKs) and expression of GPR139 inhibited these abovementioned effects.…”
Section: Mor-gpr139 Heterodimersmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR55 preferentially couples to G 12/13 and is a challenging receptor target, so further studies are required in G protein assays and relevant physiological contexts. Equally, the potential interaction of GPR55 with PAC 1 is worthy of investigation, particularly given the recent description of crosstalk between the μ‐opioid receptor and the orphan receptor GPR139 (Wang et al, ).…”
Section: New Peptide Ligands For Orphan Gpcrsmentioning
confidence: 99%
“…Interestingly, new large-scale transcriptome and proteome studies now have improved coverage of human peptides and proteins, which may also lead to the discovery of previously unappreciated protein products (Jiang et al, 2019). Orphan receptors may also require additional signalling partners that were absent from our experimental setups, such as other GPCRs or receptor activity-modifying proteins (Lorenzen et al, 2019;Wang et al, 2019). Alternatively, these receptors may not have peptide ligands or be constitutively active (Martin, Steurer, & Aronstam, 2015), or their activating molecules may be produced exogenously, as suggested for microbiome-derived ligands for GPR119 (Cohen et al, 2017).…”
Section: Bbmentioning
confidence: 99%